1998
DOI: 10.1001/archotol.124.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Analysis of Voice and Quality of Life in Patients With Laryngeal Cancer

Abstract: These data demonstrate that health status is affected by other factors than voice handicap in patients with laryngeal cancer. In addition, there is a large amount of individual variation in voice handicap after treatment. These findings illustrate the need for prospective studies assessing voice handicap and quality of life after treatment for laryngeal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
87
1
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 17 publications
6
87
1
4
Order By: Relevance
“…Furthermore, several studies on the inXuence of voice problems on quality of life revealed that in 27 up to 58% of the patients experienced diYculties in communication abilities leading to a disrupted social life [3,8,12,17,[19][20][21][22]25]. To enable quick screening on voice problems, a short 5-item voicescreening questionnaire was developed and validated, which proved to be feasible in clinical practice [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several studies on the inXuence of voice problems on quality of life revealed that in 27 up to 58% of the patients experienced diYculties in communication abilities leading to a disrupted social life [3,8,12,17,[19][20][21][22]25]. To enable quick screening on voice problems, a short 5-item voicescreening questionnaire was developed and validated, which proved to be feasible in clinical practice [22].…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed multidimensional voice analysis protocol is however recommended for monitoring voice intervention and for research purposes [24], including a structured questionnaire such as the Voice handicap index (VHI). The VHI is a validated 30-item questionnaire measuring psychosocial handicapping eVects of voice disorders [7] and is used in several studies on patients after treatment for early glottic cancer with mean VHI scores ranging from 12 to 34 points [3,8,12,19]. Most of these studies include patients with and without deviant voice quality and mean VHI data are therefore not informative on the amount of problems that patients with voice impairment after oncological treatment encounter in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…All methods of vocal rehabilitation have one major goal, that is, to achieve patient satisfaction in meeting their long-term communication needs [8]. While most literature has emphasized the immediate outcomes of alaryngeal speech acquisition, there is still a paucity of information available concerning the long-term maintenance and functional voice outcomes of the various modes of voice rehabilitation offered to both total laryngectomy and pharyngolaryngectomy patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…Even though ELS is quicker, which reduces cost considerably, many institutions prefer to use radiotherapy (1)(2)(3)(4)(5). This choice depends on the fact that the voice function and quality are better preserved after treatment (6)(7)(8)(9). Starting from this evidence many efforts have been made to find a better RT therapeutic plan.…”
Section: Introductionmentioning
confidence: 99%